Is the anterior drawer test still valuable for diagnosing mechanical ankle instability in clinical practice and research? - Luan, Lijiang; Ji, Wenxuan; Ganderton, Charlotte; Farragher, Joshua; Pappas, Evangelos; Adams, Roger David; Wang, Shasha; Han, Jia (Frontiers in Bioengineering and Biotechnology, 2025)
The anterior drawer test (ADT) has been widely used in assessing mechanical ankle instability (MAI), yet its applicability has been questioned. This study aims to clarify the clinical value of the ADT. Five databases were searched in January 2025. Studies investigating the properties of the ADT were included. Data on reliability, validity, diagnostic accuracy, and responsiveness were extracted. A total of 424 studies were screened, and 45 studies were included. The ADT generally demonstrated good to excellent intra-rater reliability, but relatively poor inter-rater reliability. Criterion validity was supported by moderate to strong correlations with imaging and anatomical measurements. The diagnostic accuracy of ADT and its variants, such as the anterolateral and reverse ADTs, showed to be generally favorable. Inconsistencies in responsiveness across studies highlighted the need for population-specific classifications and the urgent establishment of corresponding measurement standards. The manual ADT exhibited a minimal detectable change value of 1.995 mm for intra-rater reliability. Overall, the ADT provides valuable insights for diagnosing MAI, but its inter-rater reliability and accuracy may be influenced by examiners’ clinical experience and testing methods. Standardized protocols and advanced grading systems are needed to minimize inter-rater variability and enhance its result consistency, precision, and clinical utility.